Knowledge and Practice Regarding Menstrual Health among Physically Disabled Women in Kathmandu, Nepal - Pokhrel, Bishal; Mahat, Sunita; Parajuli, Kriti; Lama, Nishant (Journal of Karnali Academy of Health Sciences, 2020)
Background: Disability is the condition of difficulty in carrying out daily activities normally and in taking part in social life due to problems in parts of the body and the physical system as well as obstacles created by physical, social, cultural environment and by communication. Disability also carries stigma, so disabled people may face layers of discrimination when they are menstruating. The objective of the research is to assess the knowledge and practice regarding menstrual health of disabled women.Method: Descriptive, cross sectional study was conducted among 151 participations. Self-structured questionnaire and face-to-face interview were used as data collection tool and technique respectively. Data entry and analysis were done using SPSS version 20. Descriptive analysis like frequency and percentages were computed and presented in a table.Results: Most of participants knew 26-30 days were the normal menstrual cycle duration (80.13%). Only 31% of participants bath daily during menstruation. About 83% of participants used sanitary pad, 69.54% of participants changed pad twice a day. Maximum number (91.39%) disposed sanitary pad in dustbin. 76.82% of participants learned about menstrual hygiene from parents and friends. Majority of the participants (61.59%), cleaned the genitalia haphazardly 88.08% cleaned with soap and water Most of the respondent 90.06% had taken rest during menstruation.Conclusions: Disabled women were aware about normal duration of menstrual cycle and blood loss. However, improper practices related to menstrual health and hygiene were prevalent among disabled women, it should be timely and rightly approached to prevent and control adverse health conditions that may arise of it. Mother and peer groups could be the best choices of source of information to improve menstrual health and hygiene of differently able women.